2022
DOI: 10.1002/ueg2.12265
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome with food‐related symptoms: Future directions in the clinical management

Abstract: The majority of patients with irritable bowel syndrome (IBS) experiences foodrelated symptoms, which are associated with high symptom burden, reduced quality of life, increased healthcare consumption and reduced intake of certain nutrients.In this review we aimed to describe a clinically useful approach for physicians, by presenting the latest progress in knowledge and its translation to management in IBS patients with food-related symptoms, as well as the underlying mechanisms involved. The research tools cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The Hospital Anxiety and Depression scale contains 14 items and consists of two subscales: anxiety and depression. Each item is rated on a four-point scale, giving a maximum score of 21 for the total HADS score and anxiety and depression subscales according to Sun Cho et al [ 19 ], Melchior et al [ 20 ], and Groeger et al [ 21 ] for IBS subjects with values ≥ 8.…”
Section: Methodsmentioning
confidence: 99%
“…The Hospital Anxiety and Depression scale contains 14 items and consists of two subscales: anxiety and depression. Each item is rated on a four-point scale, giving a maximum score of 21 for the total HADS score and anxiety and depression subscales according to Sun Cho et al [ 19 ], Melchior et al [ 20 ], and Groeger et al [ 21 ] for IBS subjects with values ≥ 8.…”
Section: Methodsmentioning
confidence: 99%
“…Although its etiology is not completely understood, 2 different therapeutic approaches are available, be it with limited efficacy. 5 More than 70% of IBS patients report that their symptoms are worsened by the meal, 6 , 7 and therefore, lately, dietary interventions have gained more attention. 8 , 9 The first-line approach for the treatment of IBS consists in encouraging healthy eating and lifestyle changes 5 , 10 according to the National Institute for Health and Care Excellence (NICE) guidelines and the British Dietetic Association (BDA).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been convincingly demonstrated that diet can affect IBS, and this is the reason why many people tend to associate the various symptoms with nutrition. As a result, many patients tend to exclude certain foods from their diet on their own, or follow unsuitable nutritional patterns [ 17 , 18 ]. Although in the literature there is a lack of trials that evaluate the role of diet in the IBS-C subtype, this review aims to focus especially on the effects of fiber consumption on symptoms and microbiota.…”
Section: Introductionmentioning
confidence: 99%